fsfwerewr - Dinata, Karno; Rosidi, Ahyar; Daniyantara, Didik; Noviana, Rina; Hariadi, Hariadi; Septianwari, Hary; Najamuddin, Najamuddin; Suryansah, Suryansah (Jurnal Porkes, 2025)
This study aims to determine the effect of training using dempel weights on the speed of front kicks of PSHT fighters in Rayon MTs AL-Khaeriyah NW Semoyang. The main problem in this study is the low front kick speed shown by athletes during training and matches. The type of research used is an experiment with a descriptive quantitative approach with a one group pretest-posttes design. The population of this study were adolescent pencak silat athletes. The techniques used in data collection are tests and measurements. The instrument used is Pacing pad / sandak. The results of data analysis show an increase in the average value from 20.5 in the pretest to 28.5 in the posttest. 1 athlete scored 14% poorly, no athletes scored 0% poorly, 5 athletes scored 72% fair, 1 athlete scored 14% good and no athletes scored 0% good. The t test produces a t count of 22.362, greater than the t table of 3.588 which means there is a significant influence between training using dempel weights on front kick speed. It is concluded that training using dempe weights can significantly improve the physical abilities and performance of front kicks of pencak silat athletes.